Entropy generation associated with natural convection within a triangular porous cavity containing equidistant cold domains - Al-Waaly, Ahmed A. Y.; Tumpa, Sadia Alam; Nag, Preetom; Paul, Akshoy Ranjan; Saha, Goutam; Saha, Suvash C. (Frontiers in Energy Research, 2024)
This study investigates the computational analysis of steady, incompressible, natural convection airflow in a 2D equilateral triangular cavity featuring two stationary cold circular cylinders. The convective phenomena within the cavity have been observed under the variation of uniform porosity. The convective flow has been modeled using the Darcy-Brinkman formulations for porous medium incorporated with the Boussinesq approximation. The governing equations have been simulated using the finite element method with non-uniform triangular meshing. The investigation was conducted with a fixed Prandtl number, Pr = 0.71, and different porosity by varying Darcy number, Da = 10–5 to 10–2. The convective strength has been varied with the Rayleigh number, Ra = 103 to 106, and the length of the heated and cold segment, ε = 0.1 to 0.9. Results regarding the fluid flow and temperature distribution are visualized through streamlines and isotherms. The quantity and the quality of heat transfer (HT) have been investigated, respectively, by the Nusselt number (Nu) and the entropy generation (Egen). The results reveal that an increase in the length of the hot wall (ε) significantly reduces HT. Also, Egen increases with the length of active segments (ε), while the Bejan number (Be) consistently rises when the Darcy-Rayleigh (Da-Ra) number increases, i.e., Da-Ra≥102. The maximum HT rate was obtained within the range of Da = 10–5 to 10–3 for a constant value of ε. Furthermore, the maximum HT was obtained for the smallest value ε for any value of Da or Ra.